Levothyroxine therapy in thyroidectomized patients: ongoing challenges and controversies - Rossi, Leonardo; Paternoster, Marinunzia; Cammarata, Mattia; Bakkar, Sohail; Miccoli, Paolo (Frontiers in Endocrinology, 2025)
This mini-review provides an update on the challenges and controversies surrounding levothyroxine therapy in thyroidectomized patients, following an extensive review on dosing strategies and available formulations. Despite efforts to establish an ideal dosage adjustment method, achieving optimal thyroid hormone replacement remains complex due to interindividual variations in the hypothalamic–pituitary–thyroid axis and the pharmacokinetic and pharmacodynamic limitations of exogenous levothyroxine. Additionally, this review highlights the importance of evaluating the risk-benefit ratio of levothyroxine therapy, particularly in the setting of TSH suppression, focusing on its effects on quality of life, bone metabolism, and cardiac rhythm. Levothyroxine-induced subclinical hyperthyroidism may contribute to an increased risk of atrial fibrillation and alterations in bone mineral density, with implications that remain a subject of debate. Given the incomplete replication of endogenous thyroid hormone action by levothyroxine monotherapy, a tailored therapeutic approach is crucial. Despite ongoing research, the optimal management of thyroidectomized patients continues to be an open issue